Integrated economic efficiency and vulnerability of Chu-mango value chain in the Mekong Delta, Vietnam - Kiet, Truong Hong Vo Tuan; Sidique, Shaufique Fahmi (CentMa, 2022)
The main purpose of this study is to identify the allocation of cost, revenue, and net profit of stakeholders in marketing channels, identify vulnerable actors, and suggest policies for the sustainability of the Chu-mango value chain. This study employed value chain analysis to analyze the integrated economic efficiency of the Chu-mango value chain in the Mekong Delta, Vietnam. A total of 404 observations were collected from farmers, cooperatives, collectors, wholesalers, local retailers, export enterprises, processing firms, and supermarkets/fruit shops. The integrated economic efficiency of the Chu-mango value chain amounts to a revenue of USD 530.4 million and a net profit of USD 54.3 million. The export channels provide a revenue of USD 135.1 million and a net profit of USD 14.1 million while the domestic channels provide a revenue of USD 395.3 million and a net profit of USD 40.2 million. The findings show that farmers are the most vulnerable actors in the chain in terms of small-scale and low mango quality. This study suggests three policy initiatives: quality improvement, technological progress, and benefit re-distribution. The findings of this study contribute to the literature on value chain analysis for other tropical fruits and vegetables, and confirm the role of the value chain approach in policymaking.